Calitatea vieții - o abordare psihosociologică - Pânzaru, Petru (Calitatea Vieții, 1992)
The paper highlights the powerful dependence of the quality of life on psychological and psychosocial factors interceded by linguistic patterns and communicational nets. The author tries to sketch a theory as concerns the role of the intermediate factors within the social action and a draft of a research as regards the psychological and psychosocial impact of the language and communication upon the quality of life.